Studi Morfologi Famili Cyprinidae Di Kawasan Sungai Rungan dan Kahayan Kalimantan Tengah Indonesia - Indrian Pintacahayani Zega (Journal of Biotropical Research and Nature Technology, 2024)
Cyprinidae is a group of freshwater fish families that has more than 2,420 species that are widespread throughout the world, especially in Central Kalimantan, Indonesia. Wide distribution and the presence of geographic barriers are thought to have an impact on morphological variations in species of the Cyprinidae family. In this study we will provide information on morphological characters on three species of the Cyprinidae family (Osteocillus vittatus, Barbonymus schwanenfeldii, Labiobarbus ocellatus) originating from Central Kalimantan. Data was taken from 3 locations originating from the Kahayan and Rungan river basins, Central Kalimantan. Morphometric measurements were carried out on 14 characters which included total length, head length, tail peduncle length, head length in front of the eyes, standard length, caudal fin length, tail peduncle height, dorsal fin height, body width, eye width and mouth opening width and meristrik in 5 characters which include the number of dorsal fin rays, cloacal fins, ventral fins, pectoral fins and caudal fins. Data analysis was carried out using the Principal Component Analysis (PCA) approach using PAST software. Based on the analysis results, it shows that the three species are morphometrically significantly separated based on the characters that have been measured. This is shown by the location of the species in each quadrant because they have significant differences in character. However, every individual in each species is in the same quadrant because they have similar characters.